2020
DOI: 10.47203/ijch.2020.v32i02supp.008
|View full text |Cite
|
Sign up to set email alerts
|

Hand washing agents and surface disinfectants in times of Coronavirus (COVID-19) outbreak

Abstract: Coronavirus pandemic has led to thousands of cases and hundreds of deaths worldwide. India, too, is on the verge of this health risk at the national scale. The only measures to prevent this pandemic from spreading are physical distancing, hand hygiene, and surface disinfection, and wearing of appropriate masks. Many hand sanitizers and surface cleaning agents are being made available which are being claimed to be virucidal and to be effective against coronavirus. Here, we present a review of the hand washing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The current WHO guidance states that "thoroughly cleaning environmental surfaces with water and detergent and applying commonly used hospital level disinfectants (such as sodium hypochlorite) are effective and sufficient procedures" (58). Disinfectants are very important in the control and inactivation of microorganisms on various inanimate surfaces (61,71,72). However, if not careful, they can leave harmful residues behind on food contact surfaces.…”
Section: Disinfecting Food Contact Surfacesmentioning
confidence: 99%
“…The current WHO guidance states that "thoroughly cleaning environmental surfaces with water and detergent and applying commonly used hospital level disinfectants (such as sodium hypochlorite) are effective and sufficient procedures" (58). Disinfectants are very important in the control and inactivation of microorganisms on various inanimate surfaces (61,71,72). However, if not careful, they can leave harmful residues behind on food contact surfaces.…”
Section: Disinfecting Food Contact Surfacesmentioning
confidence: 99%
“…Cleaning with 0.5% hydrogen peroxide, 0.1% sodium hypochlorite, and 62–71% ethanol solutions have been determined to be effective on coronavirus. 148 In addition, there are many examples of fiber surfaces in most applications with coatings, as well as examples that have been applied to many surfaces such as glass, steel, and wood. In performing modifications and current structure designs of antiviral coating samples developed against COVID-19, priority was given to nanomaterials with antimicrobial properties and known antiviral effects against different viruses.…”
Section: Nanomaterial-based Coatings For the Fight Against Covid-19mentioning
confidence: 99%
“…; using disinfectants such as alcohol, soap, sodium hypochlorite, hydrogen peroxide, etc. [ 72 ]. Huang et al [ 73 ] reported that under different operation conditions, deparaffination and alcohol- and water-based disinfectants may not work completely, so there is immense need to develop disinfectants that are non-toxic and persist for longer duration.…”
Section: Nanomaterials For the Prevention Of Covid-19mentioning
confidence: 99%